The Contribution of Job Satisfaction to Organizational Commitment: The case of Universities in Al-Gezira State – Sudan - Ahmed, Dafaalla; Engdasew, Zyin (Technium Social Sciences Journal, 2021)
This paper aims to determine the contribution of job satisfaction to the organizational commitment among faculty members at Al-Gezira University and Wad Madani National University in Sudan. The study population was determined by the faculty members of public Al-Gezira University, and a questionnaire was be designed and distributed to faculty members of the university. A sample of (178) faculty members was selected at Gezira University and Wad Madani National University. The researcher took the whole staff member of the National University of Wad Madani (57). The researcher used a mixed-method research approach and use parallel mixed-method design. T-tests were used to confirming the research hypotheses. The results of the study revealed: In estimating job satisfaction’s contribution to organizational commitment, Results of the study showed: In assessing job Contribution of job satisfaction to organizational commitment among faculty members at Al-Gezira University and Wad Madani National University There is a statistical difference in the dimension of job satisfaction between the two universities in PAY (prob > chi2 =0.088). There is discrimination between males and females in the pay dimension in Al-Gezira university (prob=0.004). However, there is no statistical difference in the pay across the different academic ranks and experience levels in both universities. In general, there is a statistical difference in organizational commitment between the two universities when the general organizational commitment is considered (prob>chi2=0.818). However, there is no statistical difference in organizational commitment between the two universities with affective and normative commitments. When we examine the organizational commitment dimensional-wise we, found that organizational commitment is the same for both males and females in Al-Gezira University.